The attitudes towards, and beliefs about, physical activity in people with osteoarthritis and comorbidity: A qualitative investigation. (10th July 2021) - McKevitt, Sarah; Jinks, Clare; Healey, Emma L.; Quicke, Jonathan G.
Abstract: Objective: To investigate the attitudes towards, and beliefs about, physical activity (PA) in older adults with osteoarthritis (OA) and comorbidity to understand experiences and seek ways to improve PA participation. Methods: Semi‐structured interviews with adults aged ≥45, with self‐reported OA and comorbidity ( N  = 17). Face‐to‐face interviews explored participant perspectives regarding; (1) attitudes and beliefs about PA in the context of OA and comorbidity and (2) how people with OA and comorbidity could be encouraged to improve and maintain PA levels. Data were transcribed verbatim and inductive thematic analysis was undertaken using a framework approach. Results: Participants did not conceptualise multiple long‐term conditions (LTCs) together and instead self‐prioritised OA over other LTCs. Barriers to PA included uncertainty about both the general management of individual LTCs and the effectiveness of PA for their LTCs; and, negative perceptions about their health, ageing and PA. Participants experienced dynamic and co‐existing barriers to PA, and problematized this as a multi‐level process, identifying a barrier, then a solution, followed by a new barrier. Facilitators of PA included social support and support from knowledgeable healthcare professionals (HCPs), together with PA adapted for OA and comorbidity and daily life. PA levels could be increased through targeted interventions to increase self‐efficacy for managing OA alongside other LTCs and self‐efficacy for PA. Conclusion: People with OA and comorbidity experience complicated PA barriers. To increase PA levels, tailored PA interventions could include HCP and social support to anticipate and overcome multi‐level PA barriers and target increased self‐efficacy for LTC management and PA.